Oxidation kinetics of polyunsaturated fatty acids esterified into triacylglycerols and phospholipids in dried scallop (Argopecten irradians) adductor muscles during storage. Issue 3 (3rd March 2020) - Xie, Hongkai; Yin, Fawen; Liu, Zhongyuan; Hu, Yuanyuan; Yu, Manman; Zhou, Dayong; Zhu, Beiwei
Abstract : The difference in the oxidative susceptibility of triacylglycerols and phospholipids and the effects of the same polyphenolic antioxidant on such susceptibility in dried scallops. Abstract : The difference between the oxidative susceptibility of polyunsaturated fatty acids (PUFAs) esterified into triacylglycerols (TAG) and phospholipids (PL) and the effects of polyphenolic antioxidants on such susceptibility in dried seafood were investigated. Lipid fractions containing TAG and PL were extracted from dried scallops stored for various times, and their fatty acid contents were determined. The changes in contents of four representative PUFAs, including α-linolenic acid (ALA), arachidonic acid (AA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) esterified into TAG or PL, were used to fit kinetic models to obtain the reaction rate constant ( k ), which reflects the oxidation rates of different lipid classes. The results indicated that the oxidation of PUFAs (ALA, AA, EPA, and DHA) esterified into TAG or PL at two storage temperatures (15 °C and 25 °C) followed the first-order kinetic model, and TAG had a greater oxidation rate than PL under the experimental conditions. The results further showed that natural phenolics could effectively inhibit the oxidation of PUFAs esterified into PL and TAG, while retaining the nutritional value of dried scallops during long term storage. Furthermore, PL could be protected by the polar polyphenolic antioxidant better than TAG. This study shows that monitoring substrate loss and using kinetic models of PUFAs esterified into different lipid classes can provide insights into further chemical and nutritional studies on food systems containing complex lipid class compositions.